Middle Permian Bryozoa from the Lakaftari area, northeast of Esfahan (central Iran) - Ernst, Andrej; Senowbari-Daryan, Baba; Hamedani, Ali (Geodiversitas, 2006)
A rich bryozoan fauna is described from the Permian of the Jamal Formation, exposed in Lakaftari area, south of the town of Bagher-Abad, northeast of Esfahan (central Iran). The investigated fauna includes 31 bryozoan species: seven are described in open nomenclature, 19 are previously known, and one new genus and new species, Lakkella jamalica n. gen., n. sp., as well as four new species, Dyscritella teptosa, n. sp., Ascopora gracilis n. sp., Rectifenestella crassinodata n. sp., and Penniretepora afghanica n. sp., are described. The fauna is indicative of a middle Permian age and shows extensive palaeobiogeographic relations to the Permian of Transcaucasia, Thailand, China, Russian Platform, Indonesia, Japan and Turkey. © Publications Scientifiques du Muséum national d'Histoire naturelle.
UnivIS-Import:2017-11-07:Pub.2006.nat.dgeo.IGM.LP.middle
Keywords: Bryozoa; Central Iran; Middle Permian; New genus; New species; Paleobiogeography; Stratigraphy